Relationship between serum zinc levels and the burden of treatment in children with pneumonia - La, Qui P.; Lu, Dien T.; Le , Son H. (International Journal of Contemporary Pediatrics, 2024)
Background: Pneumonia is a common childhood disease often requiring hospitalization, with the potential for rapid progression and complications, particularly in children under five years old. Zinc plays a crucial role in various organ systems, especially the respiratory system. However, data on zinc levels and pneumonia in Vietnamese children remain limited. This study aimed to investigate the relationship between serum zinc levels and the treatment burden in children with pneumonia. Methods: A prospective observational study was conducted involving 200 children aged 2 to 59 months who were diagnosed with pneumonia and hospitalized at Can Tho Children's Hospital, Vietnam. Serum zinc levels were measured, and treatment characteristics were monitored, including the need for respiratory support, antibiotic escalation, and treatment duration. Data were analyzed using descriptive statistics, independent t-tests, simple linear regression and multivariable linear regression to determine associations between serum zinc levels and treatment outcomes. Results: Children who were not exclusively breastfed for the first six months had significantly lower serum zinc levels compared to those who were exclusively breastfed (p<0.001). Lower serum zinc levels were significantly associated with the need for respiratory support (p=0.001), antibiotic escalation (p=0.002), prolonged antibiotic use (p=0.01), and longer treatment duration (p=0.011). Multivariate linear regression revealed that each unit decrease in serum zinc levels increased treatment duration by 0.218 days (p=0.015). Conclusion: Low serum zinc levels are associated with increased treatment burden in children under five years old with pneumonia.